2012
DOI: 10.1159/000336157
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Allergy and Use of Probiotics during Pregnancy on Breast Milk Cytokines and Food Antibodies and Development of Allergy in Children until 5 Years

Abstract: Background: Whether breast milk (BM) can protect against allergy has been studied extensively, with conflicting results. Variations in mothers’ BM composition may explain some of the conflicting results. Our aim was to assess the impact of maternal allergy and probiotic intervention on BM food antibodies, transforming growth factor (TGF)-β2 and interleukin (IL)-10 and their impact on allergy development in children until the ages of 2 and 5. Methods: We measured total IgA, IgA antibodies to cow’s mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 78 publications
2
78
0
1
Order By: Relevance
“…Probiotics are defined as 'living micro-organisms which, upon ingestion in certain numbers, employ health advantage beyond inherent general nutrition' (Gorbach, 2002) and play a role in the deterrence or treatment of infectious diseases, namely, vaginal infections (Reid et al, 2009), allergies (Kuitunen et al, 2012), irritable bowel syndrome (Hoveyda et al, 2009), inflammatory bowel diseases (Damaskos & Kolios, 2008), chronically high cholesterol levels (Huang & Zheng, 2010), colitis (Resta-Lenert & Barrett, 2009) and colon cancer (Andersson et al, 2001;Liong, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are defined as 'living micro-organisms which, upon ingestion in certain numbers, employ health advantage beyond inherent general nutrition' (Gorbach, 2002) and play a role in the deterrence or treatment of infectious diseases, namely, vaginal infections (Reid et al, 2009), allergies (Kuitunen et al, 2012), irritable bowel syndrome (Hoveyda et al, 2009), inflammatory bowel diseases (Damaskos & Kolios, 2008), chronically high cholesterol levels (Huang & Zheng, 2010), colitis (Resta-Lenert & Barrett, 2009) and colon cancer (Andersson et al, 2001;Liong, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The children were followed until age 5 years and no difference in the cumulative incidence of food allergy sensitization (assessed by either a positive SPT or serum sIgE) could be found between active and placebo groups. Moreover, there were no differences on serum food-specific IgA, IgG1 or IgG4 concentrations among placebo and active groups at 2 years of age [84,85].…”
Section: Clinical Studiesmentioning
confidence: 85%
“…The children were followed until age 5 years and no difference in the cumulative incidence of food allergy sensitization (assessed by either a positive SPT or serum sIgE) could be found between active and placebo groups. Moreover, there were no differences on serum food-specific IgA, IgG1 or IgG4 concentrations among placebo and active groups at 2 years of age [84,85].It is important to note that while studies on the potential effect of maternal dietary supplement interventions with either vitamin D or PUFA are mainly observational, the studies on the effect of maternal supplementation with probiotics are randomized controlled trials. Although data point towards a lack of effect of probiotic maternal supplementation on childhood FA, when interpreting these studies, it has to be considered that the microorganisms used, doses, and durations of therapy are different.…”
mentioning
confidence: 97%
“…Many farm studies have demonstrated that child exposure to large numbers of microbes is linked to fewer allergic diseases at school age. The use of farm milk may independently protect against the development of allergies (Kuitunen et al, 2012).…”
Section: Probiotic Effects On Epigenetic Alterationsmentioning
confidence: 99%